(untitled) (Innovative professional education, 2022)
It is stated that the implementation of reforms for the development of public-private partnership in the field of vocational (vocational) education with a focus on European experience. Mechanisms for the development of public-private partnership in the field of professional (professional and technical) in relation to the labor market are proposed.